Moraxella catarrhalis: A Cause of Concern with Emerging Resistance and Presence of BRO Beta-Lactamase Gene—Report from a Tertiary Care Hospital in South India - Savitha Raveendran; Gauri Kumar; R. N. Sivanandan; Mary Dias (International Journal of Microbiology)
Background. Found as a commensal in the upper respiratory tract, Gram-negative diplococcus Moraxella catarrhalis did not hold much importance as an infectious agent for long. The emergence of the first antibiotic-resistant strain of M. catarrhalis was noted in 1977 in Sweden. This has gradually spread worldwide over the years to more than 95% of the strains showing resistance to penicillin now. Penicillin resistance is mediated by the production of beta-lactamases encoded by bro-1 and bro-2 genes that code for beta-lactamases BRO-1 and BRO-2, respectively. The purpose of this study was to explore the trends of antibiotic resistance, the presence of bro genes, and clinical correlation of these findings with the rise in M. catarrhalis infections worldwide. Methods. Strains of M. catarrhalis were isolated from the respiratory samples submitted to the microbiology laboratory. Preliminary identification was done using standard microbiological techniques, and antibiotic sensitivity was determined by minimum inhibitory concentration assessed using the E-test. Further, the genes associated with the development of resistance to penicillin (beta-lactamase enzyme) were detected using polymerase chain reaction technique. Results. Fourteen strains of M. catarrhalis were isolated during the study period. Majority of the strains were isolated from patients between 40 and 60 years of age and from males. Seasonality was observed with most strains being isolated during the winter season. The most important predisposing factors identified were advanced age with a history of smoking and chronic obstructive pulmonary disease. The antibiotic susceptibility pattern showed resistance to most antibiotics commonly used for the treatment of respiratory tract infections. Finally, all the strains were beta-lactamase producers, confirmed by the detection of bro-1 beta-lactamase gene in them. Conclusion. The increase in antibiotic resistance and beta-lactamase production in M. catarrhalis is a cause of concern. The emerging resistance pattern emphasises the need for an appropriate antibiotic stewardship program in clinical practice. Importance should be given to the monitoring of the trends of antibiotic susceptibility and their usage to prevent the emergence of outbreaks with resistant strains and treatment failures.